Systems modelling in cattle production - an application in Botswana - Cartwright, T.C.; Anderson, F.M.; Buck, N.G.; Nelsen, T.C.; Trail, J.C.M.; Pratchett, D.; Sanders, J.; Astle, W.; Light, D.E.; Rennie, T.W.; Rose, T.J.; Shorrock, C. (1982)
Discusses use of mathematical modelling as a research tool to evaluate alternative practices, illustrating its application in beef cattle production systems in Botswana, with a description of data inputs, model utilized & simulations carried out. Compares actual & simulated values and examines effect of variant weaning ages on productivity.